Does initial high efficacy therapy in multiple sclerosis surpass escalation treatment strategy? A comparison of patients with relapsing-remitting multiple sclerosis in the Czech and Swedish national multiple sclerosis registries - Hrnciarova, Tereza; Drahota, Jiri; Spelman, Tim; Hillert, Jan; Lycke, Jan; Kubala Havrdova, Eva; Recmanova, Eva; Adamkova, Jana; Mares, Jan; Libertinova, Jana; Pavelek, Zbysek; Hradilek, Pavel; et al. (Multiple sclerosis and related disorders, 2023)
BACKGROUND: In relapsing-remitting multiple sclerosis (RRMS) the most common treatment strategy has been to start with low-moderate efficacy disease modifying therapy (LE-DMT) and to escalate to more efficacious treatments in cases of breakthrough disease activity. However, recent evidence suggests a better outcome in patients commencing with moderate-high efficacy DMT (HE-DMT) immediately after clinical onset. OBJECTIVE: The aim of this study is to compare disease activity and disability outcomes in patients treated with the two alternative strategies using the Swedish and Czech national multiple sclerosis registries, taking advantage of the fact that the relative frequency of each strategy differs markedly between these two countries. METHODS: Adult RRMS patients who initiated their first-ever DMT between 2013 and 2016 and were included in the Swedish MS register were compared with a similar cohort from the MS register of the Czech Republic using propensity score overlap weighting as a balancing method. The main outcomes of interest were time to confirmed disability worsening (CDW), time to achieve an expanded disability status scale (EDSS) value of 4, time to relapse, and time to confirmed disability improvement (CDI). To support the results, a sensitivity analysis focusing solely on patients from Sweden starting with HE-DMT and patients from the Czech Republic starting with LE-DMT was performed. RESULTS: In the Swedish cohort, 42% of patients received HE-DMT as initial therapy compared to 3.8% of patients in the Czech cohort. The time to CDW was not significantly different between the Swedish and Czech cohorts (p-value 0.2764), with hazard ratio (HR) of 0.89 and a 95% confidence interval (CI) of 0.77-1.03. Patients from the Swedish cohort exhibited better outcomes for all remaining variables. The risk of reaching EDSS 4 was reduced by 26% (HR 0.74, 95%CI 0.6-0.91, p-value 0.0327), the risk of relapse was reduced by 66% (HR 0.34, 95%CI 0.3-0.39, p-value <0.001), and the probability of CDI was three times higher (HR 3.04, 95%CI 2.37-3.9, p-value <0.001). CONCLUSION: The analysis of the Czech and the Swedish RRMS cohorts confirmed a better prognosis for patients in Sweden, where a significant proportion of patients received HE-DMT as initial treatment.
Keywords: recidiva; Registries; Švédsko; Registry study; Humans; Multiple Sclerosis; registrace; Sweden; dospělí; Escalation strategy; lidé; High-efficacy DMT; Adult; Multiple sclerosis; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; roztroušená skleróza; Czech Republic; Recurrence; Česká republika